THE ADVANTAGES OF USING AUTHENTIC MATERIALS IN TEACHING ECONOMIC TERMINOLOGY - ABDUSAIDOVA, Gulhayo Bakhriddin kizi (The Lingua Spectrum, 2025)
This article outlines the pedagogical benefits of using meaningful and authentic materials like economic reports, news articles, financial statements, and market analyses to teach economic terms, with a focus on economic terminology. For instance, authentic materials allow for the contextualized acquisition of vocabulary and subject matter awareness such as the English for Economics teaching concepts (or skills) which help learners become familiar with and better understand language.